2022
DOI: 10.1002/ddr.21982
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol: A lead compound that inhibits SARS‐CoV‐2 replication, the activity of viral and human cysteine proteases, and virus‐induced IL‐6 secretion

Abstract: The global emergence of coronavirus disease 2019 (COVID‐19) has caused substantial human casualties. Clinical manifestations of this disease vary from asymptomatic to lethal, and the symptomatic form can be associated with cytokine storm and hyperinflammation. In face of the urgent demand for effective drugs to treat COVID‐19, we have searched for candidate compounds using in silico approach followed by experimental validation. Here we identified celastrol, a pentacyclic triterpene isolated from Tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…46 Compared to M pro , there have been far fewer publications describing studies attempting to find PL pro inhibitors. For example, one study identified disulfiram and analogues 47 as covalent inhibitors and another described the natural product celastrol, 48 which binds similarly to PL pro , M pro , and cathepsin L. Yet, another natural product, anarcardic acid, is a weak inhibitor of PL pro and M pro . 49 An initial hit for PL pro came from the naphthalene derivative GRL-0617, which had previously been identified for SARS-CoV and demonstrated activity against SARS-CoV-2.…”
Section: ■ Discussionmentioning
confidence: 99%
“…46 Compared to M pro , there have been far fewer publications describing studies attempting to find PL pro inhibitors. For example, one study identified disulfiram and analogues 47 as covalent inhibitors and another described the natural product celastrol, 48 which binds similarly to PL pro , M pro , and cathepsin L. Yet, another natural product, anarcardic acid, is a weak inhibitor of PL pro and M pro . 49 An initial hit for PL pro came from the naphthalene derivative GRL-0617, which had previously been identified for SARS-CoV and demonstrated activity against SARS-CoV-2.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In vitro [271][272][273][274] AD: Alzheimer's disease; PD: Parkinson's disease; HMGB1: high mobility group box 1 protein.…”
Section: Prevents Oxidative Stressmentioning
confidence: 99%
“…More importantly, a previous in vitro study reported that TP could bind to the main protease (M pro ) and receptor-binding domain (RBD) of SARS-CoV-2 and is able to reverse gene expression signature and inhibit the virus replication in SARS-CoV-2-infected cells. 21 Echoing these findings, we managed to assess the therapeutic value of TP lipo for the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%